2004
DOI: 10.1029/2003ja010076
|View full text |Cite
|
Sign up to set email alerts
|

Geosynchronous magnetic field response to solar wind dynamic pressure pulse

Abstract: We present a study of the response of the geosynchronous magnetic field to abrupt enhancements of the solar wind dynamic pressure. Results are obtained separately for cases of northward and southward interplanetary magnetic field (IMF) prior to and after the solar wind pressure jump. For pressure enhancements with southward IMF we find that the response of the geosynchronous magnetic field on the dayside is mostly compression. However, on the nightside it can be a dipolarization‐like change that is similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 23 publications
6
73
1
Order By: Relevance
“…In recent years, much work has been done on how pressure enhancements influence aurora activity Kamide, 1998, 2001;Zhou and Tsurutani, 1999;Lyons et al, 2000;Zesta et al, 2000;Chua et al, 2001;Boudouridis et al, 2003]. Also, some authors investigated its effect on the geosynchronous magnetic field [Wing et al, 2002;Lee and Lyons, 2004]. However, the effect of the solar wind dynamic pressure on the development of the storm time ring current has received almost no attention until the recent work by Wang et al [2003].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much work has been done on how pressure enhancements influence aurora activity Kamide, 1998, 2001;Zhou and Tsurutani, 1999;Lyons et al, 2000;Zesta et al, 2000;Chua et al, 2001;Boudouridis et al, 2003]. Also, some authors investigated its effect on the geosynchronous magnetic field [Wing et al, 2002;Lee and Lyons, 2004]. However, the effect of the solar wind dynamic pressure on the development of the storm time ring current has received almost no attention until the recent work by Wang et al [2003].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Wang et al (2007) concluded that the IMF orientation does not affect the geosynchronous response significantly (see also Figure 2a). Kuwashima and Fukunishi (1985) and, more recently, Lee and Lyons (2004) suggested that midnight events associated with southward IMF orientations were often characterized by a dipolarization-like change similar to that one occurring during substorms, while the dayside response was mostly compressional; for northward IMF, a compression of the entire magnetosphere was generally observed, with few cases of depression near midnight. Lee and Lyons (2004) suggested that the magnetosphere is very sensitive to small SW pressure enhancements when the IMF is strongly southward for a long period of time.…”
Section: The Role Of the Sw Parametersmentioning
confidence: 99%
“…Kuwashima and Fukunishi (1985) and, more recently, Lee and Lyons (2004) suggested that midnight events associated with southward IMF orientations were often characterized by a dipolarization-like change similar to that one occurring during substorms, while the dayside response was mostly compressional; for northward IMF, a compression of the entire magnetosphere was generally observed, with few cases of depression near midnight. Lee and Lyons (2004) suggested that the magnetosphere is very sensitive to small SW pressure enhancements when the IMF is strongly southward for a long period of time. Focusing attention on the midnight sector, Wang et al (2009) concluded that ≈75% of the negative responses were associated with southward IMF orientations.…”
Section: The Role Of the Sw Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that although PE serves as a good metric when the magnetic field has large variations, such as the ground and geosynchronous magnetic field variations during storms (e.g., Pulkkinen et al, 2010), it tends to exaggerate a small inconsistency if the field responses (the denominator) are weak. Usually, B responds more apparently near noon (typically tens of nT) than in the nightside (usually several nT) (Lee and Lyons, 2004), and the variations of the smaller components (B x and B y ) are weaker. Therefore, PE might have some limitations in validating the model responses around the mid-night and for the minor components.…”
Section: Prediction Efficiencymentioning
confidence: 99%